Early life microbiome disbalance impacts neuroendocrine outcomes in pre-pubertal mice in a sexually dimorphic manner - Nankova, Bistra B.; Hu, Furong; LaGamma, Edmund F. (Frontiers in Microbiology, 2025)
IntroductionAdverse exposures during perinatal development disrupt the emerging gut microbial ecology that in turn negatively influences long term health. How gut dysbiosis affects complex neurobehavioral functions or even simple reflex arcs (e.g. the amplitude of sympathoadrenal adaptive responses to hypoglycemia) in the extrauterine environment is not well understood.MethodsThe C57Bl6 dams were given broad-spectrum antibiotics in the drinking water at parturition until weaning of their litter to perturb the normal seeding and maturation of the postnatal microbiome, control animals received sterile water. To evaluate the impact of altered postnatal flora the offspring were subjected to behavioral tests or sacrificed after exposure to insulin-induced hypoglycemia. Fecal samples were collected for microbial whole genome shotgun taxonomic profiling and predictive functionality. As an index of host sympathoadrenal capacity, individual adrenal medulla samples from each group were subjected to RNA sequencing to identify differentially expressed genes between the groups and gain insights into molecular pathways contributing to the observed outcomes. Given that several neurodevelopmental disorders in humans are biased by sex we also included it as variable in this report.ResultsThe offspring of control dams displayed sex-specific differences in microbiome composition, exploratory behavior, adrenal transcriptome profiles and basal urinary epinephrine levels. Maternal antibiotics during nursing caused: (1) microbial dysbiosis in the offspring as evident by markedly enlarged ceca, no detectable by-products of bacterial fermentation (sp. SCFA) and dramatic changes in microbial composition, diversity (reduced - alpha Chao1and beta Bray-Curtis, as compared to their respective controls) and predictive metabolic activity; (2) alteration in the transcriptional signature of the adrenal medullae and attenuated peripheral stress responses in male offspring, associated with gap junction signaling pathways; (3) increased anxiety-like testing metrics, and decreased locomotor activity; all in a sexually dimorphic manner.DiscussionWe speculate that the observed sex differences in the gut microbiome may contribute to neurodevelopmental disorders known to have sex-related disparities and in the capacity for successful adaptation to stress. A better understanding of how microbial communities and their hosts interact during critical portions of postnatal neurobehavioral development may help personalize nutritional and therapeutic strategies to promote long term health.